The duty of fair representation – effective protection for individual rights in collective agreements? - Adell, B. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author uses the example of Fisher against Pemberton to illustrate the case of an individual employee action against his union for breach of the union*s duty of fair representation.